PENDIDIKAN IPS DALAM MEMBENTUK SDM BERADAB - Adi S, Wahyu (LPPM STKIP PGRI Bandar Lampung, 2019)
Education is very important in human life, therefore it must receive more serious attention. In this regard, education is a system to improve the quality of human life in all aspects of life, as well as an effort to inherit cultural values ​​for human life. Social studies education is an integral part of the national education system which aims to build good citizens. Through social studies education, it is hoped that civilized human resources (HR) will be formed, namely human resources who are educated (knowledgeable and skilled) and cultured (strong character).